Implementasi Surat Perjanjian Menurut Hukum Perdata dan Kebiasaan Masyarakat Adat (Desa Cinta Maju Kabupaten Samosir) - Imman Yusuf Sitinjak; Sariaman Gultom; Christian Daniel Hermes; Mariah SM Purba (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
This community service is because seeing the situation in the area has problems regarding the implementation of the agreement, especially regarding the pawning of agricultural land, the implementation of this service aims to provide understanding, evaluate problems in the community and seek to provide solutions to problems that exist in the community, especially regarding agreements in the village of Cinta Maju, Samosir Regency. The method of implementing community service is carried out in an identical way, namely the lecture and question and answer method, which provides an understanding of the theoretical agreement. With this service activity, it provides a new perspective on the implementation of the agreement in the village. It is also hoped that through this service, the village will become a place for the development of higher education education in the study of problems both in the field of law and in other fields of education